Money or Prestige? Legal Proceedings Concerning Vančura’s Authorship of Obrazy z dějin národa českého - Jiroušek, Bohumil (Theatrum historiae, 2010)
The contribution deals with the legal proceedings concerning Vladislav Vančura’s Obrazy z dějin národa českého authorship, the legal proceedings was conducted in the 1970’s and 1980’s. Vladislav Vančura was writing this book at the end of the 1930’s, while some papers (historical facts) were submitted by young historians Václav Husa, Jaroslav Charvát and Jan Pachta. Vančura was executed during World War II but his collaborators became important representatives of the official Marxist-Leninist historiography after 1948. Above mentioned historians claimed their collaboration with Vladislav Vančura as an es- sential piece of Marxist historiography concerning the Czech history, and they also claimed a part of the royalty. Vladislav Vančura’s heirs and the publishing house refused further payments in the 1970’s and Marie Husová (Václav Husa’s widow) initiated legal proceed- ings (1972-1984). The legal proceedings were concluded by the statement that their contri- bution did not create an original work, the Marxist historians submitted only word-for-word excerpts of older, non-Marxist historiography. Besides the fact, that the Czechoslovak Marxist-Leninist Historiography founders lost their money, the litigation resulted into the fact that they also suffered moral disgrace.